Users' perceptions of blog functions: educational vs personal use. Issue 1 (28th January 2014) - Yueh, Hsiu-Ping; Lin, Weijane; Lu, Tzuyi
Abstract : Purpose: – This paper aims to understand how users' perceptions of the different functions of blogs vary in educational use and personal use, and further to explore whether experience with blogs has an influence on differences in perceptions of blog functions. Design/methodology/approach: – To empirically determine whether the blog functions were suitable for educational and personal use, a blog system with numerous functions was constructed for users to evaluate. In total, 48 college students were recruited to participate in the study. The participants navigated this system and then filled in a questionnaire to give their opinions on the functions of both educational blogs and personal blogs. Findings: – The findings of this study indicate that of the 26 blog functions, perceptions of 20 of the functions differed significantly between educational and personal use. Moreover, the results showed that only two blog functions, backup and traffic source, were influenced by both blog experience and blog usage. Originality/value: – This study distinguishes itself from the previous studies on blogging systems in its specific focus on functionality with detailed evaluation under different purposes of contexts. Practical suggestions are accordingly made for practitioners to choose when and which functions to use under different circumstances to enhance the interaction and information exchange between users in the field practice of educational blogging.